The Influence of Attitudes, Safety, and Quality on Interest in Subscribing Halal Cosmetic Products - Satria, Akbar Dimas; Indra, Indra (AL-FALAH : Journal of Islamic Economics, 2024)
Purpose: This study aims to analyze the effect of consumer attitudes, safety, and product quality on interest in subscribing to halal cosmetic products, with a focus on generation Z considering the trend and public awareness of halal products, especially cosmetics, is increasing every year.Design/Method/Approach:Â  This study uses a quantitative approach with a questionnaire as an instrument to collect primary data from 108 generation Z respondents who have used halal cosmetic products in Riau Province, and applies Structural Equation Modeling Partial Least Square (SEM - PLS) analysis techniques.Findings:Â  This study uses a quantitative approach with a questionnaire to collect data from 108 generation Z respondents in Riau Province who use halal cosmetic products, and applies SEM-PLS for data analysis. The results show that generation Z consumer attitudes and product quality have a positive and significant influence on the interest in subscribing to halal cosmetic products with coefficient values of 0.430 and 0.439, respectivelyOriginality/Values: These findings provide important insights for the halal cosmetics industry in designing more effective marketing strategies to meet the needs of generation Z consumers who are increasingly concerned about halal products, as well as to expand market share in this industry.